Applications of Social Media in the Tourism Industry: A Review - Islam, Md. Tariqul (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose- This study aims to review and analyze the articles related to social media applications and their impact on the tourism industry. Methodology- For conducting this study, three leading databases named Google Scholar, Science Direct, and EBSCO Host were used for data collection purposes, and the research was conducted in three phases. Selecting the database for collecting data was the first phase, which was carried out during the period between November 2020 to December 2020. In the second phase, screening of the collected data was done, and in the final stage, 46 articles were selected to conduct this study. Discussion- Over the last decade, the rapid advancements in information and communication technology (ICTs) have had reflective impacts on the global tourism sector. Both researchers and professionals have acknowledged that social media applications have a significant impact on both suppliers and consumers of the tourism industry. Findings- Based on the reviewed articles from the perspectives of the tourism consumers as well as the tourism suppliers, this study has found that consumers use social media in pre-during-post travel for searching different information and suppliers generally use social media for promotion, communication, management, research purposes.